2009
DOI: 10.3732/ajb.0900049
|View full text |Cite
|
Sign up to set email alerts
|

An Early Cretaceous fruit with affinities to Ceratophyllaceae

Abstract: A new genus and species with affinities to Ceratophyllaceae from the Lower Cretaceous of Kansas, USA is reported. The fruits of Donlesia dakotensis gen. et sp. nov. are smooth achenes with two winged lateral spines, two winged facial spines, one stylar spine, and a long peduncle with a distinctive groove. The facial spines are arranged perpendicular to the lateral spines. The seed contains two cotyledons and a central plumule. Dichotomous leaves associated with Donlesia dakotensis fruits are whorled, petiolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…The aquatic environments of the Lower Cretaceous probably were not very different from those in later ages, so there was little pressure for change over time. We find fossils even more similar to the extant Ceratophyllum in the late Albian (28). These fossils also support an ancient age for the Ceratophyllum lineage and suggest a more basal position for this lineage, as found in some recent phylogenetic analyses (24,25).…”
Section: Discussionsupporting
confidence: 59%
“…The aquatic environments of the Lower Cretaceous probably were not very different from those in later ages, so there was little pressure for change over time. We find fossils even more similar to the extant Ceratophyllum in the late Albian (28). These fossils also support an ancient age for the Ceratophyllum lineage and suggest a more basal position for this lineage, as found in some recent phylogenetic analyses (24,25).…”
Section: Discussionsupporting
confidence: 59%
“…Fossils from the eastern shoreline of the Western Interior Seaway preserve an extensive record of Early Cretaceous plants, one that has been studied for more than a century (Lesquereux, 1891). The angiosperms have been particularly well studied from the eastern shore of the seaway (Lesquereux, 1891;Dilcher and Crane, 1984;Wolfe and Upchurch, 1987;Upchurch and Dilcher, 1990;Wang and Dilcher, 2006a,b;Hu et al, 2008;Dilcher and Wang, 2009;Wang and Dilcher, 2009;Wang et al, 2011;Wang et al, 2013). Initial analysis of the level of angiosperm species richness suggested that there were 437 distinct species (Lesquereux, 1891), which is an extremely high number and skews diversity curves for this time period (Lidgard and Crane, 1990).…”
Section: Introductionmentioning
confidence: 97%
“…At present, it is difficult to determine whether these simple flowers reflect a common ancestry or independent reduction due to adaptation to anemophily and hydrophily. Excavation of chloranthoid and ceratophyllaceous flowers or fruits from the Lower Cretaceous indicates that these simple flowers have had a long history (Friis et al, 1986; Dilcher & Wang, 2009). Given that the sister relationship between Ceratophyllum and Chloranthaceae has been recovered in two well‐designed mitochondrial gene phylogenetic studies and a series of analyses of carefully constructed morphological matrices, it may be premature to dismiss this result, as was done in the recently published APG III (Angiosperm Phylogeny Group, 2009).…”
mentioning
confidence: 99%